MANAJEMEN LEMBAGA PENDIDIKAN ISLAM DILIHAT SEBAGAI PERILAKU ORGANISASI: Kepemimpinan Pendidikan, Model Kepemimpinan, Kepemimpinan Abad 21 - Fadla Robbi; Skrghnm Alim; Muawanah (Kelola: Journal of Islamic Education Management, 2026)
This article examines the management of Islamic educational institutions from an organizational behavior perspective, with particular emphasis on educational leadership, leadership models, and the demands of 21st-century leadership. The management of Islamic educational institutions involves not only planning, organizing, directing, and controlling institutional resources, but also integrating Islamic values such as trust (amanah), justice, exemplary conduct, and cooperation into all organizational activities. This integrative approach contributes to the development of an adaptive organizational culture while preserving the Islamic identity of educational institutions. From an organizational behavior perspective, institutional effectiveness is strongly influenced by attitudes, motivation, values, and work behavior of organizational members. Educational leadership plays a strategic role, as leaders function not only as administrative decision-makers but also as moral and spiritual role models who shape organizational culture and professional commitment. Various leadership models including transformational, collaborative, situational, and Islamic value-based leadership are discussed as effective approaches to enhancing teacher motivation, professional development, and the internalization of moral and religious values within educational practices. Furthermore, 21st-century leadership in Islamic educational institutions requires adaptive, innovative, collaborative, and digitally literate competencies. Leaders are expected to act as agents of change who facilitate pedagogical innovation, data-informed decision-making, and sustainable institutional development, while maintaining ethical and spiritual integrity. This study employs a qualitative library research approach by analyzing relevant scholarly articles through content analysis. The findings indicate that the integration of Islamic educational management, organizational behavior, and leadership models is essential for strengthening institutional effectiveness, adaptability, and moral character. This article offers a conceptual framework that connects management practices, organizational behavior, and leadership competencies as a foundation for developing resilient and value-oriented Islamic educational institutions in the 21st century. Keywords: Islamic educational management, organizational behavior, educational leadership, leadership models, 21st-century leadership.